Case report of a novel injection molded two-piece ceramic dental implant surgery with immediate loading - Zago Sá Fortes, Rafael; Speck, Guilherme Lobo; Julio, Gillian Luis Andrade (Brazilian Journal of Implantology and Health Sciences, 2024)
This paper aims to briefly review the use of zirconia implants, question the particular indications of these kind of implants and to demonstrate the usage of a novel injection molded two-piece ceramic dental implant from Neodent system (Neodent Zi Implant, Curitiba, Brazil) in a patient presenting a tooth fracture. The implant was performed in a single stage procedure: tooth extraction, implant placement and restoration with a peek abutment and provisional tooth.